Enterprise maturity and successful business process orientation projects - Soares,Carlos Alberto Pereira (2018)
According to business process management (BPM), organizations should be oriented to optimize their business processes using the best technology available. Strategic management maturity (SMM) can be understood as the stage the organizations achieve when they use the best practices related to strategy to their business area. Business process orientation (BPO) stimulates the BPM effort and uses BPM as reference and tool. In this article, it is suggested that BPO projects using BPM information to have a successful impact depends on the SMM level of the organization where the project happened. A research was conducted in eleven Brazilian companies. Seven variables were used to measure the SMM level and four variables to evaluate the impact of the BPO projects. The conclusion was that the higher the SMM level of company, the higher is the positive impact of the BPO project.